Synthesis, crystal structure and photoluminescence properties of Eu2+-activated RbCaGd(PO4)2 phosphors. Issue 14 (27th January 2016) - Chen, Xue; Wang, Qidi; Lv, Fengzhu; Chu, Paul K.; Zhang, Yihe
Abstract : RbCaGd(PO4 )2 :Eu 2+ was prepared by the Pechini-type sol–gel method. The crystal structure was determined in the first time. The dipole–dipole interaction plays a major role in the mechanism of concentration quenching of Eu 2+ in this phosphor. Abstract : A series of novel double-phosphate compounds RbCaGd(PO4 )2 :Eu 2+ were first synthesized by the Pechini-type sol–gel method, and their structure and luminescence properties were characterized in detail. The compound RbCa0.97 Gd(PO4 )2 :0.03Eu 2+ crystallizes in the hexagonal system with space group P 62 22 and the parameters a = 7.006(49) Å, c = 6.358(80) Å, and V = 269.969 Å 3, Z = 1. Its crystal structure is similar to that of hexagonal LnPO4, where the Rb atom occupies a large tunnel in the lattice and the Ln position is statistically occupied by both Gd and Ca (Eu) atoms. In addition, RbCaGd(PO4 )2 :Eu 2+ produces an intense broadband emission from 400 to 600 nm with the CIE coordinates near (0.2089, 0.2674) and assembles a broad excitation spectrum from 250 to 425 nm. The concentration quenching, crystal field splitting, critical energy transfers distance and thermally stable luminescence properties of RbCaGd(PO4 )2 :Eu 2+ phosphors are all discussed, which indicate that this material can be considered as a promising bluish green phosphor for application in white-light UV LEDs.